A robust numerical method for modeling multiple wells in city-scale geothermal field based on simplified one-dimensional well model. (August 2019) - Wang, Guiling; Liu, Guihong; Zhao, Zhihong; Liu, Yanguang; Pu, Hai
Abstract: An efficient numerical model, which can simulate the coupled fluid flow and heat transfer processes in geothermal fields, is essentially required to evaluate the fate of geothermal wells and the temperature and pressure evolutions of geothermal reservoirs in response to the long-term well operations. Due to the scale disparity between wells and geothermal reservoirs (∼dm vs. ∼km), very fine mesh is required to accurately represent the highly-dynamic zones near geothermal wells, and thus the conventional geothermal reservoir model including geothermal wells is usually time consuming. To improve the computational efficiency without losing accuracy, a simplified one-dimensional geothermal well model considering heat convection and conduction along well axis and heat transfer between geothermal fluid and rocks in the radial direction is proposed and incorporated into the geothermal reservoir model. Both a bench-mark example and a case study of Beijing city geothermal field are presented to demonstrate the reasonability and efficiency of the proposed reservoir modeling method. The computational time are significantly reduced because of avoiding mesh refinement near geothermal wells. The multiple wells effects, interactions between different reservoirs, and the role of faults in reservoir performance are also discussed based on the case study of Beijing city geothermal field. Graphical abstract: Image 1 Highlights: Simplified model for geothermal well based on equivalent heat transfer coefficient. An integrated reservoir-well model for geothermal field including multiple wells. Robust prediction of the fate of geothermal wells in Beijing urban geothermal field.